Cloud computing and firm growth - Destefano, Timothy; Kneller, Richard; Timmis, Jonathan (Nottingham, 2019)
"The arrival of the cloud has enabled a shift in the nature of ICT use, from investment in sunk capital to a pay-on-demand service that allows firms to rapidly scale up. This paper uses new firm-level data to examine the impact of cloud on firm growth in the UK, using zipcode-level instruments of the timing of high-speed fibre availability and expected speeds. We find cloud leads to the growth of young firms in terms of employment and productivity, but they become more concentrated in fewer plants. For older firms we find no scale or productivity growth, but instead disperse activity by closing plants and moving employment further from the headquarters. In addition, the plants that close tend to be those without access to fibre broadband."